KUAT LENTUR PANEL DINDING EXPANDED POLYSTYRENE DENGAN PERKUATAN KALSIUM SILIKAT DAN PENYAMBUNG GESER BAUT - Bella Lutfiani Al Zakina; Ashar Saputra; Ali Awaludin (TEKNISIA, 2019)
Started from an innovative construction system programmed by the government to provide residential homes in 2007 that is the use of expanded polystyrene concrete as a wall construction. This type of construction provides advantages that can reduce the risk of damage in the earthquakes because it has a relatively light weight which is one of the requirements for earthquake resistant houses. For this reason, the bearing capacity of the wall panel is increased to become an earthquake resistant wall using reinforcement layers. Variations on this research are expanded polystyrene concrete panels without reinforcement, with reinforcement, and with reinforcement and bolt shear connectors. Strengthening uses a reinforcement of Calcium Silicate are Kalsi board. Testing based on SNI 03-3122-1992 (Fibrous Lightweight Concrete Panel). The results showed that the average value of the panel densities was 612,57 kg/m3, the elastic modulus was 942,37 MPa, compressive strength of 2,52 MPa and water absorption capacity of 12,11%. The highest flexural strength was obtained by the panel with kalsiboard reinforcement of 1,60 MPa. This results the addition of reinforcement layers will affect the increase in strength.